Morinda officinalis oligosaccharides alleviate chronic unpredictable mild stress-induced depression through the BDNF/TrkB/CREB pathway and symptoms of sexual dysfunction in mice - He, Mengjie; Hu, Mengying; Wang, Tingqiao; Zuo, Zeping; Li, Hongkai; Zhao, Zhiwei; Hao, Yunwen; Dai, Xueling; Wang, Jianfang; Sun, Yaxuan (Frontiers in Neuroscience, 2025)
BackgroundIn recent years, depression has become a global public health concern, and one of the common concomitant symptoms are diminished sexual motivation and impaired sexual performance. The aim of this study was to investigate the potential effects of Morinda officinalis oligosaccharides (MOO) on depression and its concomitant symptom, sexual dysfunction.MethodsChronic unpredictable mild stress (CUMS)-induced depression model was constructed, and the effects of MOO on depression and sexual abilities were evaluated.ResultsThe results revealed that MOO was able to alleviate CUMS-induced depression-like behavior in mice, to inhibit hippocampal neuron apoptosis, to reverse monoamine neurotransmitter imbalance, increase Brain-derived neurotrophic factor (BDNF) expression levels in the hippocampus, to modulate the composition and distribution of gut microbiota, and to increase the abundance of probiotics after continuous gavage of MOO for 28 days. MOO further confirmed that sexual dysfunction is closely related to the development of depression by improving the lack of sexual motivation and low sexual performance in CUMS-induced depressed mice, modulating the disruption of sex hormone secretion in serum, and alleviating sperm morphology and functional defects in the epididymis.ConclusionThese findings on MOO provide a basis for exploring its antidepressant mechanism, its use to improve hypogonadotropic symptoms, and for future development of new antidepressant drug to improves hypogonadotropic symptoms.